ANALISIS BIBLIOMETRIK KEPEMIMPINAN PEMERINTAHAN DALAM TRANSFORMASI DIGITAL - UTAMI, YUANITA; SARTIKA, IKA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This bibliometric study focuses on mapping research on government leadership in digital transformation based on Scopus data. This study was conducted to determine the development of research on government leadership in digital transformation. Data collection was carried out based on the Scopus database with the keywords leadership, digital transformation, and e-government, publication categories in the form of articles. Data analysis was carried out descriptively based on the year of publication, publisher name, country of affiliation, author affiliation, researcher productivity, and research trends. The Scopus search engine was used to obtain accurate research development data. The database was cleaned to obtain keywords by reducing typing errors in the same term using the OpenRefine application. Data analysis was carried out using VOSViewer and Biblioshiny. The results of the study illustrate that the trend of publications on government leadership in digital transformation from 2017-2024 experienced an increase in publications of 26 articles in 2024. The author whose article was most cited was Miskiewicz R., 2022 with 60 citations. The article with the most citations is entitled Clean and Affordable Energy within Sustainable Development Goal: The Role of Governance Digitalization published in 2022. Indonesia is the most cited country with 9 articles in 2022 and has the highest author affiliation. VOSViewer and Biblioshiny visualizations also show that research on government leadership in digital transformation that is still rarely studied is related to central government, citizen participation, stakeholder integration, e-readiness, and collaborative intelligence. ABSTRAKPenelitian bibliometrik ini berfokus pada pemetaan penelitian kepemimpinan pemerintahan dalam transformasi digital berdasarkan data Scopus. Penelitian ini dilakukan untuk mengetahui perkembangan penelitian kepemimpinan pemerintahan dalam transformasi digital. Pengumpulan data dilakukan berdasarkan Scopus database dengan kata kunci leadership, digital transformation, dan e-government, kategori publikasi berupa artikel. Analisis data dilakukan secara deskriptif berdasarkan tahun publikasi, nama penerbit, negara afiliasi, afiliasi penulis, produktivitas peneliti, dan tren penelitian. Mesin pencarian Scopus digunakan untuk mendapatkan data perkembangan penelitian yang akurat. Database dibersihkan untuk mendapatkan kata kunci dengan mengurangi kesalahan pengetikan dalam istilah yang sama dengan menggunakan aplikasi OpenRefine. Analisis data dilakukan dengan menggunakan VOSViewer dan Biblioshiny. Hasil penelitian menggambarkan bahwa tren publikasi kepemimpinan pemerintahan dalam transformasi digital dari tahun 2017-2024 mengalami peningkatan publikasi sebanyak 26 artikel pada tahun 2024. Penulis yang artikelnya paling banyak disitasi adalah Miskiewicz R., 2022 dengan 60 kali kutipan. Adapun artikel dengan sitasi terbanyak berjudul Clean and Affordable Energy within Sustainable Development Goal: The Role of Governance Digitalization yang terbit tahun 2022. Indonesia menjadi negara yang paling banyak disitasi sejumlah 9 artikel pada tahun 2022 dan memiliki afiliasi penulis tertinggi. Visualisasi VOSViewer dan Biblioshiny juga menunjukkan bahwa penelitian kepemimpinan pemerintahan dalam transformasi digital yang masih jarang diteliti adalah terkait dengan central government, citizen participation, stakeholder integration, e-readiness, dan collaborative intelligence.